Exploring the aglycon promiscuity of a new glycosyltransferase from Pueraria lobata. Issue 13 (30th March 2016) - Sun, Lili; Chen, Dawei; Chen, Ridao; Xie, Kebo; Liu, Jimei; Yang, Lin; Dai, Jungui
Graphical abstract: Highlights: A new glycosyltransferase, PlGT7, was cloned from Pueraria lobata . PlGT7 exhibits aglycon promiscuity and catalyzes O -, S -, N -glycosidic bond formation. PlGT7 can be exploited as a versatile biocatalyst for structural glycorandomization. Abstract: Enzymatic glycosylation catalyzed by glycosyltransferases has great potential for creating bioactive glycosylated small-molecule compounds. Here, we highlight the aglycon promiscuity of a new glycosyltransferase (PlGT7) from Pueraria lobata . PlGT7 exhibited the capability to glycosylate 26 structurally diverse drug-like scaffolds and simple phenolics with UDP-glucose to form O -, S -, and N -glycosides. The reversibility of PlGT7 coupled with its substrate flexibility was also exploited to generate bioactive glucosides with simple sugar donor. These studies indicate the significant potential of an enzymatic approach to the glycosylation of bioactive natural and unnatural products in drug discovery.